Enhancing Efficiency in Solar Construction Projects through Lean Methodologies - Pingulkar, Chinmay; Vadlamani, Satish; Kumar, Ashish; Goel, Om; Agarwal, Raghav; Jain, Shalu (Journal of Quantum Science and Technology (JQST), 2024)
The solar construction industry faces significant challenges in efficiency, project timelines, and resource utilization. This paper explores the application of Lean methodologies to enhance operational efficiency in solar construction projects. Lean principles, which prioritize value creation and waste minimization, can be effectively integrated into various phases of solar project management. By adopting tools such as Value Stream Mapping (VSM), Just-In-Time (JIT) inventory management, and continuous improvement practices, solar construction teams can streamline workflows, reduce delays, and optimize resource allocation. This study presents a framework for implementing Lean methodologies tailored to the unique demands of solar construction. It highlights case studies that demonstrate successful Lean interventions, illustrating tangible improvements in project delivery times and cost reductions. Additionally, the paper discusses the cultural shift required for teams to embrace Lean practices, emphasizing the importance of stakeholder engagement and training. By fostering a Lean mindset, organizations can not only enhance their efficiency but also contribute to sustainable practices within the solar energy sector. The findings of this research underline the potential of Lean methodologies to transform solar construction projects, paving the way for more efficient and effective deployment of renewable energy solutions. This paper aims to serve as a guide for industry practitioners seeking to improve project outcomes through Lean principles, ultimately supporting the broader goal of increasing renewable energy adoption.